2007
DOI: 10.1088/1674-0068/20/06/773-778
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Magnetic Properties of Ag/Fe/Ag Pseudo-Sandwich Nanogranular Films

Abstract: Nanogranular Ag/Fe/Ag films were prepared by magnetron sputtering from a silver and an iron target onto glass substrates at room temperature and subsequent in situ annealing. The structural and magnetic properties of the films were investigated as a function of silver layer thickness and annealing temperature. X-ray diffraction shows the Fe(110) peak is formed in all the samples. Vibrating sample magnetometer measurements indicate that the magnetic moments lie well perpendicular to the film plane. Coercivity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It has been reported that Ag is a good buffer layer for FePt and CoPt recording media [6,7]. Peng et al reported the effects of Ag layer thickness on magnetic properties and microstructure of Ag/Fe/Ag granular films [8]. It is speculated that Ag is probably also a kind of ideal buffer layer material for Fe medium.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Ag is a good buffer layer for FePt and CoPt recording media [6,7]. Peng et al reported the effects of Ag layer thickness on magnetic properties and microstructure of Ag/Fe/Ag granular films [8]. It is speculated that Ag is probably also a kind of ideal buffer layer material for Fe medium.…”
Section: Introductionmentioning
confidence: 99%
“…Structural and magnetic properties were probed in Fe/Cu multilayers for varied Fe layer thickness [16]. Interlayer diffusion of nonmagnetic metals C, Cr, Pt [17,18], Ag [19], Al and Cu into the magnetic layers has been studied [20]. Some Mn-based alloys and compounds exhibited ferromagnetism though they did not contain ferromagnetic elements.…”
Section: Introductionmentioning
confidence: 99%